Enzymatic formation of a skipped methyl‐substituted octaprenyl side chain of longestin (KS‐505a): involvement of homo‐IPP as a common extender unit - Taro Ozaki; Shinde, Sandip S.; Gao, Lei; Okuizumi, Ryo; Liu, Chengwei; Ogasawara, Yasushi; Lei, Xiaoguang; Dairi, Tohru; Minami, Atsushi; Oikawa, Hideaki (Angewandte Chemie, 2018)
Longestin (KS‐505a), a specific inhibitor of phosphodiesterase, is a meroterpenoid that consists of a unique octacyclic terpene skeleton with branched methyl groups at unusual positions (C1 and C12). The biochemical analysis of Lon23, a methyltransferase involved in the biosynthesis of longestin, demonstrated that methylation of IPP afforded 3Z‐3‐methyl IPP. This compound as well as IPP was selectively accepted as extender units by Lon22, a geranylgeranyl diphosphate (GGPP) synthase homolog, to yield dimethylated GGPP (dmGGPP). Absolute configuration of dmGGPP was determined to be (4R, 12R) by degradation and chiral GC analysis. These findings led us to propose key steps of the biosynthetic pathway of the unusual homoterpenoid longestin.